2007
DOI: 10.1177/0016986207302722
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Curriculum Effectiveness in Social Studies

Abstract: This quasi-experimental study examines the effects on student performance of a Javits-funded curriculum designed to respond to the needs of high-ability students in elementary and middle school social studies. The curriculum, implemented with all students in heterogeneous classrooms, addresses state standards while integrating advanced content, higher level process emphases, and a conceptual orientation. Data collection focuses on student performance in conceptual reasoning, critical thinking, and content lear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
37
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 17 publications
5
37
0
Order By: Relevance
“…Yet our history suggests that this is not true-that some organizational models like special classes and schools have proven their viability as contexts where differentiated curriculum is best delivered; that using a differentiation model within subject areas allows for the most effective reorganization of curriculum for the gifted, using differentiated materials as the tool; and that multiple program offerings are essential to adequately address the needs of a diverse group of learners. These conclusions have been well documented in the literature of the field (Little, Feng, VanTassel-Baska, Rogers, & Avery, 2007;Neihart, 2007;Sternberg, Torff, & Grigorenko, 1998).…”
Section: The Need To Build On the Past Rather Than To Destroy Its Foosupporting
confidence: 68%
“…Yet our history suggests that this is not true-that some organizational models like special classes and schools have proven their viability as contexts where differentiated curriculum is best delivered; that using a differentiation model within subject areas allows for the most effective reorganization of curriculum for the gifted, using differentiated materials as the tool; and that multiple program offerings are essential to adequately address the needs of a diverse group of learners. These conclusions have been well documented in the literature of the field (Little, Feng, VanTassel-Baska, Rogers, & Avery, 2007;Neihart, 2007;Sternberg, Torff, & Grigorenko, 1998).…”
Section: The Need To Build On the Past Rather Than To Destroy Its Foosupporting
confidence: 68%
“…This review also found that the needs of many gifted and talented students are not addressed in many regular classroom settings across our country Moon et al, 1995;Reis et al, 2004;Reis & Purcell, 1993;Westberg et al, 1993). Classroom teachers can, however, learn to differentiate curriculum and instruction in their regular classrooms and to implement gifted education strategies and pedagogy, such as acceleration (Colangelo et al, 2004), content and instructional differentiation and enrichment, and interest-based projects across all content areas (Field, 2009;Gavin et al, 2007;Little et al, 2007;Reis et al, 2007;Reis, Gentry, & Maxfield, 1998;Reis, Westberg, et al, 1998;Tieso, 2002).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Reis et al (1997) Talents in two places: Case studies of high ability students N = 12 currently enrolled college or university students PS Gifted students with learning disabilities in this study encountered many negative experiences in school, often failed to be identified as either gifted or learning disabled, and half had psychological problems that required professional help and support in subsequent years. Little et al (2007) A study of curriculum effectiveness in social studies N = 1200 (Treatment-941 Comparison-251)…”
Section: Research Synthesesmentioning
confidence: 99%
See 2 more Smart Citations